Health and women in Latin America and the Caribbean : old issues and new approaches - Gomez Gomez, Elsa (UN SantiagoCL, 1997)
Attempts to map out a profile of women's situation in Latin America and the Caribbean with respect to health in the early 1990s. Focuses on situations that affect women exclusively or differently and pays particular attention to situations that imply gender inequities.